(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article explores the role of vitagenic learning strategies in the development of students’ critical thinking skills. Vitagenic education emphasizes the use of learners’ life experiences as a valuable educational resource, enabling them to connect theoretical knowledge with real-life situations. The study examines the pedagogical foundations of vitagenic learning and its effectiveness in fostering analytical thinking, problem-solving abilities, independent decision-making, and reflective learning. The findings suggest that integrating students’ personal experiences into the educational process enhances engagement, promotes deeper understanding, and contributes significantly to the development of critical thinking competencies required in the twenty-first century.